OPTIMALISASI KUALITAS CITRA ANATOMI DENGAN VARIASI IDOSE DAN INTERATIVE MODEL RECONTRUCTION (IMR) PADA MSCT UROGRAPHY NON KONTRAS DENGAN TEKNIK TRACKING - Nanang Sulaksono; Ary Kurniawati (Perhimpunan Radiografer Indonesia (PARI), 2023)
ABSTRAK Background: The urinary tract (urinary system) consists of the two kidneys and ureters, the urinary bladder, and the ureters. There are several ways to examine abnormalities in the urinary tract radiologically. including the current CT scan, CT Scan (MSCT) is one of the modalities to evaluate and diagnose urinary tract disorders. MSCT of the urinary tract without using positive contrast media is able to identify images of the urinary tract in cases of urolithiasis. iDose and Interative Model Reconstruction (IMR) are the second generation of IR algorithms from the previous generation, namely iDose. This technology can also lower the dose to the patient and also improve the quality of the resulting image. Method: This type of research is an experiment with an observational approach with comparisons. This type of research is an experiment with data obtained from a comparison of noise values and the quality of anatomical images from tracking images with iDose and IMR variations. And an assessment was carried out by 3 radiologists. Place of data collection in radiology RSUD RAA Soewondo Pati. Time for data collection From April to November 2022. in assessing anatomical images using statistical tests. Data analysis was carried out using the Wilcoxon statistical test method because the data were ordinal with paired groups. The Wilcoxon statistical test was used to test the hypothesis and see the level of difference in anatomical image information. The level of significance (level of significance) is 95% or α> 0.05 and is done by assessing the p-value. For a significant level of assessment p <0.05 then Ho is rejected and p> 0.05 then Ho is accepted. Results: Friedman test on each anatomical part of the urinary tract system on Non-Contrast Urography MSCT images with Tracking Techniques with iDose 1-6 and IMR 1-3 variations, there are differences in anatomical image information with a p value of .000 (p <0.05). In the anatomy of the renal parenchyma, the highest mean rank is iDose 3 with a value of 8.15. In pelvic anatomy and kidney calices, the highest mean rank is at iDose 6 with a value of 8.05. In ureteral anatomy, the highest mean rank is iDose 3 with a value of 8.05. In the anatomy of the perirenal space, the highest mean rank is iDose 3 with a value of 8.20. Based on the results of the mean rank Friedman test to find out the optimal I Dose and IMR values, it was obtained iDose 1 with a mean rank value of 4.65, iDose 2 with a mean rank value of 4.95, iDose 3 with a mean rank value of 8.3, iDose 4 with a mean rank value of mean rank 6.4, iDose 5 with a mean rank value of 6.55, iDose 6 with a mean rank value of 7.75, IMR 1 with a mean rank value of 1.65, IMR 2 with a mean rank value of 2.05, and IMR 3 with a mean value rating 2.7. Conclusion: Changes in the values of iDose and IMR variations affect the anatomical image information of Non-Contrast MSCT Urography with Tracking Techniques, this is based on the results of the mean rank Friedman test performed on each anatomy of the renal parenchyma, pelvic calices, ureters and perirenal space which shows a difference. Based on the results of Friedman's mean rank test conducted on the entire anatomy of the renal parenchyma, ureters, and perirenal space, it showed that the optimal iDose and IMR variation values were iDose 3 with a mean rank value of 8.3.